Functional DNA-based hydrogel intelligent materials for biomedical applications. Issue 10 (19th February 2020) - Zhou, Liping; Jiao, Xiangyu; Liu, Songyang; Hao, Mingda; Cheng, Siyang; Zhang, Peixun; Wen, Yongqiang
Abstract : Multifunctional intelligent DNA hydrogels have been reviewed for many biomedical applications. Abstract : Deoxyribonucleic acid (DNA) nanotechnology is a relevant research field of nano-biotechnology, which has developed rapidly in recent years. Researchers have studied DNA far more than they have studied its genetic characteristics, and now it has evolved into the field of nanomedical materials. A variety of articles based on DNA nanostructures can be obtained by rational design and controllable preparation. In particular, intelligent DNA-based hydrogel materials have attracted significant attention as an essential representative of macro DNA materials. They have shown a wide range of applications, especially in the field of biomedical applications. DNA-based hydrogels have many unique and fascinating properties, such as, excellent biocompatibility, biodegradability, basic programmability, catalytic activities, therapeutic potential, and molecular recognition and bonds. The intelligent DNA hydrogel will undergo abrupt changes in the stimulation of temperature, pH value, ionic strength, and solvent composition. These factors can also be used for applications in intelligent materials that play an essential role in biomedical sciences. To date, intelligent DNA hydrogels have been reported for many applications, including controlled drug delivery, targeted gene therapy, cancer therapy, biosensors, protein production, and 3D cell cultures. However, the large-scale production of intelligent DNA hydrogels has not yet been realized, and the synergistic multifunctional integration has not been explored. This review summarizes the current state of DNA nanostructures, especially the intelligent DNA-based hydrogel materials, and focuses on design and engineering for bio-responsive use and proposes some reasonable prospects for the future development of intelligent DNA-based hydrogel materials.